2014
DOI: 10.7763/ijcea.2014.v5.422
|View full text |Cite
|
Sign up to set email alerts
|

Studies Regarding the Florisil Impregnation with Ionic Liquid through Ultrasonication

Abstract: Abstract-The paper presents the studies regarding the impregnation of Florisil with Cyphos IL-101 using a new method of impregnation instead of the classic methods: the ultrasonication. In order to determine the efficiency of the ultrasonication methods of impregnation, the work conditions were varied, and the obtained supported ionic liquids were characterized through scanning electron microscopy (SEM), energy dispersive XRay analysis (EDX) and FTIR-Fourier transform infrared spectroscopy. From the experiment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…It was observed that in order to obtain a stable and homogenous impregnation of the solid support with the studied IL, it is not necessary to increase the ultrasonication time, but a higher amplitude should be used. Increasing the ultrasonication time leads to the conglomeration of the IL particles on the solid support afecting in this way the reproducibility of the adsorption experiments [63]. Increasing the amplitude of sonication assures an easier transmission of the IL particles through the liquid media until it reaches the cavities of the solid support.…”
Section: Figurementioning
confidence: 99%
“…It was observed that in order to obtain a stable and homogenous impregnation of the solid support with the studied IL, it is not necessary to increase the ultrasonication time, but a higher amplitude should be used. Increasing the ultrasonication time leads to the conglomeration of the IL particles on the solid support afecting in this way the reproducibility of the adsorption experiments [63]. Increasing the amplitude of sonication assures an easier transmission of the IL particles through the liquid media until it reaches the cavities of the solid support.…”
Section: Figurementioning
confidence: 99%
“…Recently, to overcome at least some of these drawbacks, ether-functionalised ILs, the so-called TSILs, have been synthesised. 23,24 For the past decade, numerous green routes including reaction under solvent-free conditions 25 using non-classical techniques such as ultrasonication, 26 microwaves and others 27,28 have been adopted for the synthesis of ILs. Microwave (MW)-assisted synthesis has been used to develop a rapid green synthetic route, resulting in large reductions in reaction time (from hours to minutes), uniform temperature and pressure during the course of the reaction and better yields.…”
Section: Introductionmentioning
confidence: 99%